Services quality on grassroots football clubs in the region of Murcia. An application of the importance-performance analysis - Martínez-Caro, E.; Martínez-Caro, E.; Díaz-Suardíaz A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2014)
Grassroots football clubs, key in the promotion of sport in school term, like any sport organization, must increase user satisfaction by offering high quality services. This research proposes a quality assessment in order to design an improvement plan which shows evidence of overinvestment resource areas, areas of insufficient resources, and to make a proposal of improvement actions. With this aim, a questionnaire based on the SERVQUAL scale was administered to a sample of 1076 users of grassroots football clubs in the Region of Murcia, including 413 players, 366 parents, 207 coaches and 90 referees. The results indicated that the strengths of grassroots football clubs in the Region of Murcia are mainly in aspects of responsiveness and assurance. The weak points, however, are resources investment in attributes less important to users, related to assurance and empathy.